Customer interaction in service innovation: seldom intensive but often decisive. Case studies in three business service sectors. (1st January 2011) - Kuusisto, Arja; Riepula, Mikko
The purpose of this study was to develop the yet limited empirical knowledge on the intensity of customer interaction and on specific customer roles in service innovation processes. An empirical study of 12 business service innovation projects was conducted in cleaning and security, financial, and ICT services. Overall, direct customer interaction in service development can be characterised as being limited and focused on specific, well-defined tasks in these service sectors, which offer support services to their customers. In the analysis, three highly important customer roles emerged: 1 customers act as catalysts of service development processes 2 customer feedback is often decisive in nature, allowing for go/kill decisions and directing other key decisions 3 customers have a key role in internal marketing of the new service idea within the provider organisation. The study also proposes a new variant of a concurrent service innovation process to existing service innovation literature.